REASONS FOR BIFURCATION OF THE LEGAL DISCOURSE BASIS (SYNERGETIC AND PHILOSOPHICAL-LINGUISTIC APPROACHES) - Kharchenko, Yulia; Kharchenko, Sergii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
The key task of this study is the conceptualization of the phenomenon of legal discourse, as well as, the analysis of bifurcation trends that affect the basic directions of its development. As a result of the study, it was confirmed that the sustainable development of global legal systems is subject to random deviations due to the virtualization of law and the semantization of legal discourse. Two or more new states of legal systems become unstable. Virtual law and real law "overlap" each other, and in such a legal reality separate protocols operate and the impression is created that such a model of legal discourse is dominating. At the same time, the mechanisms of self-regulation of the legal system support it in two states, and the transition to one or another trajectory becomes difficult. The conclusions demonstrate that the foundations of legal discourse are inevitably transformed, developed, violated, taking into account the peculiarities of social development. This is reflected most expressively in the language of law. The reformatting of the legal system is due to the infinitely complex combination of the influence of the subjects of law on it and the quality of their legal actions.